2021
DOI: 10.1007/s10457-021-00611-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the yield and profitability of intercropped walnut systems in Croatia

Abstract: In Croatia, farmers are showing increasing interest in establishing walnut orchards for nut production on arable land due to higher anticipated net margins. One way to address the lack of profitability in the initial years when nut yields are low may be to plant arable intercrops. The anticipated impacts of this practice were assessed using a biophysical simulation model (Yield-SAFE) to determine the growth and yield of crops and trees in arable, orchard, and silvoarable systems, and an economic farm model (Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
1
Order By: Relevance
“…These were also the most productive cases when looking at the yields on a square metre basis, so even though the ratio of sown area was lower, the higher yields compensated the ’field loss’ on a hectare basis. Likewise, Žalac et al [ 15 ] also reported high relative crop yields in a grain maize–barley–rapeseed rotation in a walnut alley cropping system, with LER values 1.05–1.14 in years 1, 4 and 7, predicted by the Yield-SAFE model. In that study, a simulation of maintaining the system for 20 years resulted in LER 1.38–1.53 depending on the number of trees per hectare (170 and 100 trees, respectively).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…These were also the most productive cases when looking at the yields on a square metre basis, so even though the ratio of sown area was lower, the higher yields compensated the ’field loss’ on a hectare basis. Likewise, Žalac et al [ 15 ] also reported high relative crop yields in a grain maize–barley–rapeseed rotation in a walnut alley cropping system, with LER values 1.05–1.14 in years 1, 4 and 7, predicted by the Yield-SAFE model. In that study, a simulation of maintaining the system for 20 years resulted in LER 1.38–1.53 depending on the number of trees per hectare (170 and 100 trees, respectively).…”
Section: Discussionmentioning
confidence: 90%
“…Another case is when fruit trees are grown in the alley cropping system, and thus no data on timber is recorded. In research conducted in Croatia [ 15 ], maize, barley and rapeseed were grown between allies of walnut trees with different tree planting densities per hectare (170, 135 and 100 trees ha −1 ), using the Farm-SAFE and Yield-SAFE models. However, the analyses focused on walnut fruit and not on the timber production.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations